2019
DOI: 10.3390/ijerph16111895
|View full text |Cite
|
Sign up to set email alerts
|

Study on the In Vitro Activity of Five Disinfectants against Nosocomial Bacteria

Abstract: Nosocomial infections cause significant morbidity and mortality worldwide, and the pathogenic organisms responsible for such infections can develop resistance to antimicrobial agents. Understanding the activity of disinfectants against clinical and environmental bacterial isolates is therefore crucial. We analysed the in vitro activity of five antimicrobial products (phenolic compounds, didecyldimethylammonium chloride (DDAC), sodium hypochlorite, isopropanol + ammonium compounds (IACs), hydrogen peroxide) aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
2
19
0
6
Order By: Relevance
“…Other studies have already demonstrated the effect of different biocidal agents against the microorganisms tested in this study, showing that the efficacy of the disinfection process varies with the type of disinfectant [ 99 , 100 ] or according to the application method used [ 101 , 102 ]. There are few reports in the scientific literature on the efficacy of PPE decontamination after exposure to pathogens, as was analyzed in this study.…”
Section: Discussionmentioning
confidence: 82%
“…Other studies have already demonstrated the effect of different biocidal agents against the microorganisms tested in this study, showing that the efficacy of the disinfection process varies with the type of disinfectant [ 99 , 100 ] or according to the application method used [ 101 , 102 ]. There are few reports in the scientific literature on the efficacy of PPE decontamination after exposure to pathogens, as was analyzed in this study.…”
Section: Discussionmentioning
confidence: 82%
“…The biocidal effect of hydrogen peroxide is attributable to the-OH radical, formed by the decomposition of peroxide in the presence of catalysts, such as iron and copper ions, commonly found in microorganisms. The radical acts via an oxidative mechanism against the membrane, DNA and other cellular constituents of the microorganism (Montagna et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, some alternatives for efficient ARG removal from effluent of wastewater treatment plants have been recently proposed, including the use of synthesized hydrated manganese oxide coupled with permanganate, the metal-free photocatalyst graphitic carbon nitride (g-C 3 N 4 ), and the natural zeolite clinoptilolite enriched with silver (AgNZ) [ 56 , 57 , 58 ]. In addition, bacterial resistance to commonly used disinfectants is often overlooked [ 59 ].…”
Section: Summary Knowledge Gaps and Conclusionmentioning
confidence: 99%